European guidelines for workplace drug and alcohol testing in hair. Issue 10 (12th July 2016) - Salomone, A.; Tsanaclis, L.; Agius, R.; Kintz, P.; Baumgartner, M. R.
Abstract : Guidelines for Legally Defensible Workplace Drug Testing have been prepared and updated by the European Workplace Drug Testing Society (EWDTS). They are based on the 2010 version published by Pascal Kintz and Ronald Agius (Guidelines for European workplace drug and alcohol testing in hair. Drug Test . Anal .2010, 2, 367) and in concordance with the Society of Hair Testing guidelines (Society of Hair Testing guidelines for drug testing in hair. Forensic Sci . Int .2012, 218, 20‐24). The European Guidelines are designed to establish best practice procedures whilst allowing individual countries to operate within the requirements of national customs and legislation. The EWDTS recommends that all European laboratories that undertake legally defensible workplace drug testing use these guidelines as a template for accreditation. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The aim of this paper is to present the 2015 finished update of guidelines issued by EWDTS for workplace drug testing in hair. The document is focused on fundamental aspects of general interest, requirements involved and operational instructions. The new guidelines take into account both the technical progress and new developments in the drug market. Cut‐offs and instruction for collection are also provided.